Geriatric urology - Griebling, Tomas Lindor (Springer New York, 2014)
Geriatric urology represents one of the largest overall sectors of care provided within the specialty of urology. As the incidence and prevalence of many clinical urologic conditions increase significantly in older adults, the practice of urology involves a need for advanced knowledge of the basic principles of geriatrics. Geriatric Urology outlines important topics in the care of elderly urology patients. The first section covers the biology of aging, changes in the genitourinary system, and common diseases including urologic conditions that may serve as warning signs of other disorders. Section two covers geriatric syndromes and implications for urologic care including frailty, polypharmacy, dementia, , and wound healing. Urologic conditions in older adults are explored in detail including urinary incontinence, pelvic organ prolapse, urinary tract infection, nocturia, and benign prostate diseases. Other topics covered include obtaining informed consent, development of advance directives, palliative medicine and care of the dying patient. Geriatric Urology is of great value to urologists, geriatricians, internists, residents and family practitioners.